2007
DOI: 10.1017/s0033583508004654
|View full text |Cite
|
Sign up to set email alerts
|

Protein folding and misfolding: mechanism and principles

Abstract: Two fundamentally different views of how proteins fold are now being debated. Do proteins fold through multiple unpredictable routes directed only by the energetically downhill nature of the folding landscape or do they fold through specific intermediates in a defined pathway that systematically puts predetermined pieces of the target native protein into place? It has now become possible to determine the structure of protein folding intermediates, evaluate their equilibrium and kinetic parameters, and establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
267
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(280 citation statements)
references
References 165 publications
(289 reference statements)
13
267
0
Order By: Relevance
“…The folding model pictured in Fig. 5B is identical to the extensively worked out case of cytochrome c for which a series of HX NMR studies defined four native-like foldon-based intermediates in a well-ordered pathway (24)(25)(26). It also is consistent with the finding of individual nativelike intermediates in many other proteins.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The folding model pictured in Fig. 5B is identical to the extensively worked out case of cytochrome c for which a series of HX NMR studies defined four native-like foldon-based intermediates in a well-ordered pathway (24)(25)(26). It also is consistent with the finding of individual nativelike intermediates in many other proteins.…”
Section: Discussionsupporting
confidence: 77%
“…In the initial on-pathway step, a limited structural unit is assembled by a relatively unguided amino acid search (59), which makes the first on-pathway step the intrinsically slow step. In subsequent steps in which amino acid searching can be informed by existing structure, a faster assisted folding mode emerges called "sequential stabilization" (25,60). Like the process of coupled folding upon binding (61)(62)(63)(64), the prior structure will selectively guide and stabilize the units with which it interacts in the native protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reynolds and coworkers showed that (1) the folding rate correlates extremely closely with total contact distance evaluated only over the lock residues, and (2) the lock residues tend to have high ϕ-values, "as would be expected for residues that play an important role in the transition structure for folding" (Chintapalli et al 2010). Reynolds further suggests that the closed loop hypothesis is able to give an alternative description of the data obtained by Englander's group (Bai et al 1995;Hoang et al 2003;Englander et al 2007) for cytochromes c and b562 (as well as for triosephosphate-isomerase) initially interpreted in terms of independent folding units (foldons). The closed loop hypothesis-based mechanism was said to be "as elegant as the published explanations as it does not invoke discontinuous foldons."…”
Section: O'neill Et Al (O'neill and Robert Matthews 2000)mentioning
confidence: 95%
“…The two-state model is an invaluable tool in protein folding studies, and has provided significant insight into how both local and global properties of proteins influence their folding rates. [1][2][3] However, as a result of its simplicity, the two-state model provides only a snapshot (often through inferences made by perturbing the transition state ensemble 4 ; of the folding pathways that connect D to N, 5,6 and does not address kinetic features such as transient intermediates and kinetic traps. 7 Moreover, description of heterogeneity among partly folded states and folding via parallel pathways are both outside the confines of the two-state approximation.…”
Section: Introductionmentioning
confidence: 99%